Mechanical behavior of materials with a compact hexagonal structure obtained by an advanced identification strategy of HCP material, AZ31B-H24 - R. Harbaoui; O. Daghfas; A. Znaidi; V. Tuninetti (Fracture and Structural Integrity)
The use of magnesium alloys, in particular AZ31B-H24, represents an increasingly important aspect in the transport field, as well as in the aeronautical industry. In the forming processes of this material, the shapes of the product are obtained by plastic deformation. Therefore, it is important to know the properties of plastic behavior to optimize these shaping processes. The properties of this alloy are strongly influenced by its complex microstructure which can be modified by plastic deformation. For this purpose, in this work an identification strategy is established beginning with the elastoplastic orthotropic law based on the choice of an equivalent stress, a hardening law and a plastic potential. Thus, the anisotropic behavior of the magnesium sheet is modeled using CPB06 criterion with four hardening laws then later compared to Barlat91 criterion. Once the model is validated, it would therefore be useful to study the plastic behavior of AZ31B-H24 from an experimental database.